Modeling the Determinants and Effects of Creativity in Advertising - Smith, Robert E.; MacKenzie, Scott B.; Yang, Xiaojing; Buchholz, Laura M.; Darley, William K. (Marketing Science, 2007)
Consumer perceptions of advertising creativity are investigated in a series of studies beginning with scale development and ending with comprehensive model testing. Results demonstrate that perceptions of ad creativity are determined by the interaction between divergence and relevance, and that overall creativity mediates their effects on consumer processing and response.